Enhancing Students` Speaking Skill through Task-Based Language Teaching (TBLT) at English Tadris Department of STAIN Kerinci - Mudra, Heri (AT-TALIM, 2016)
This paper reports a classroom action research which conducted in an EFL classroom. The problem of this study is that teaching and learning process tends to be monotonous due to the single method used by English teachers. The learners` speaking course is familiarized with English structures. It requires a communicative and constructive method such as TBLT. The purpose of this study is to describe the effectiveness of TBLT in enhancing students` speaking skill. 30 EFL learners at the seventh semester at STAIN Kerinci took a part in this study. The instruments used to collect the data were speaking test, observation, and field-note. The results of the study showed that there were 2 cycles needed to implement the method. The process of teaching and learning in the first cycle indicates that TBLT improved learners` speaking skill, though some problems were needed to be solved. Unlike the cycle I, the process in the cycle II was improved in term of learners` speaking score and their motivation to attend the course if compared with those in cycle I. So, it is concluded that TBLT is an appropriate method to improve learners` speaking skill.